Unemployment as a macroeconomic problem: causes, types, and ways to mitigate its effects ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes the main types of unemployment, the causes of its emergence, and the diverse consequences for society and the economy. Special attention is given to a comprehensive approach to solving the problem, which includes measures to stimulate economic growth, develop human capital, and improve the institutional environment.
Keywords: economy; unemployment; labormarket; employment